The future of marine fisheries management and conservation in the United Kingdom: Lessons learnt from over 100 years of biased policy. (January 2023) - Kemp, Paul S.; Subbiah, Gowshika; Barnes, Richard; Boerder, Kristina; O'Leary, Bethan C.; Stewart, Bryce D.; Williams, Chris
Abstract: Marine wild-capture fisheries depend on the capacity of the ocean to provide a flow of harvestable resources to sustain the industry. Paradoxically, conventional fishing often undermines these resources by degrading the environment and overexploiting fish stocks. Many UK fisheries have declined for over a century due to a biased focus on their social-economic value and lack of recognition that they are social-ecological systems and need to be managed as such. With the UK's recent transition to an independent coastal state, the Fisheries Act (2020) and associated Joint Fisheries Statement provide an opportunity to correct this. Focusing on the ecological foundations, a more sustainable future for UK fisheries may be achieved by: (1) implementing a conservative quota setting system based on Maximum Sustainable Yield (MSY), defined as that which would occur when the biomass of a population of the target species is at 50% of that estimated at carrying capacity, to set catch limits rather than targets. The biomass of fish stocks should be allowed to regenerate to a minimum of 120% of that which will achieve MSY to provide a buffer against the uncertainty in ecological response to climate change. (2) Fishing capacity should be reduced while redistributing a greater share of the quota to sectors of the fleet that are demonstrably more sustainable; recognising that short term compensation may be required by some to mitigate the impacts of displaced activity until the benefits of stock recovery are realised. (3) Greater restrictions should be applied to ensure the most damaging fishing techniques ( e.g. bottom trawling and dredging) are prohibited as appropriate in the network of marine protected areas. Protection should be enforced to promote the regeneration of degraded habitats and restoration of fish populations to help achieve the objectives as set out in the Act.